• Difficults face medical Students in learning Medical Terminology (Comprehensive Journal of Science, 2026)
This study  aims to shed on some of the difficults that face medical  students at High Institute   of medical science and Technologies  Almarj in learning medical terminology.  It  relies on information gathered from a medical English vocabulary test, which consists of three questions. The primary findings indicate that medical students struggle with the medical English language, which constitutes the source of the challenges medical English language that represents the source of difficulties that medical students encountered and thus impede understanding medical terminology. The study concluded that the areas of difficulties include the translating and writing of these definitions They should Focus on some relatively current medical courses in English for academic purposes. They should also use a good dictionaries especially medical dictionaries
Keywords: Medical Terminology, English for Specific Purposes (ESP), Learning Difficulties, Medical Students, High Institute Almarj, Translation